Penerapan Upah Sistem Bagi Hasil dan Penyerapan Tenaga Kerja - Ade Onny Siagian (PT FORMOSA CENDEKIA GLOBAL, 2022)
Reducing unemployment and then creating productive jobs are the two biggest barriers in most developing countries. However, the achievements of the two programs face a dilemma. On the one hand, broad job creation leads to a decrease in labor compensation. On the other hand, increasing labor compensation implies that employers will change their production techniques to be capital intensive (i.e. lay off their workers). This study tests the hypothesis that workers whose compensation packages contain a profit-sharing component are less prone to being laid off in the face of negative shocks to product demand than workers who are paid a fixed time-based wage. The theory is tested on macroeconomic data, particularly on two selected manufacturing industries in Indonesia. The estimation results show that the profit sharing meets the theoretical requirements to stabilize employment. This means that profit sharing can be considered as a means to combat unemployment.